Karakteristik Organoleptik dan Kandungan Formalin Pada Ikan Asin DI Pasar Kota Malang - Carmenita Maharani Aditiya; Ratih Tyas Widara; Fendi Yoga Wardana; Ita Handayani (STIKes Ibnu Sina Ajibarang, 2024)
The use of formalin as a food additive has been prohibited by the Ministry of Health as stipulated in The Indonesia Ministry of Health Regulation No.1168/MENKES/PER/X/1988 regarding the food additive. However, there is still widespread use of formaldehyde as a preservative in food such as salted fish persists. This research aims to identify the formaldehyde content in salted fish sold by vendors at Pasar Gadang, Malang City. The samples are tested qualitatively using organoleptic tests, KMnO4 test method, formalin kit, and Tollens reagent and then continued with the UV-visible spectrophotometry test to determine the formalin levels in the samples. Qualitative test results showed that all test samples contained formalin. Quantitative test results showed that the average level of formalin in the sample was 200 mg/kg. All test samples contained formalin at levels exceeding 0.2 mg/kg.